Prosthetops wolfbergensis sp. nov.—a giant amongst the ‘minute moss beetles’, with new data on other members of the genus (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2013)
Prosthetops wolfbergensis sp. nov. (Coleoptera, Hydraenidae) is described from the Western and Northern Cape regions of South Africa; the new species, at up to 4.2 mm total length, apparently being the longest ‘minute moss beetle’ described to date. Prosthetops species are characteristic inhabitants of temporary rainwater pools and seepages on exposed plateau in the Cape fold mountains, and on rock outcrops beside streams and rivers. New collection records and ecological data are given for members of the genus, and the female of Prosthetops pronotus Perkins & Balfour-Browne, 1994 is described and illustrated for the first time.